ANALISIS PENERAPAN STANDAR AKUNTANSI KEUANGAN EMKM PADA PENYUSUNAN LAPORAN KEUANGAN UMKM DI KECAMATAN SAYUNG KABUPATEN DEM AK - Lutfiyah, Inayatul; Andini, Rita; Lestari, Utami Puji (STIE Semarang, 2024)
Discovering how MSMEs in Sayung District use the Accounting Standards for Micro, Small and Medium Entities (SAK EMKM) to compile their financial reports is the main objective of this study. This study employed a mixed-methods approach to data analysis. It collected data from MSME players in Sayung District using questionnaires and direct interviews. A method known as purposive sampling is used in the sampling process. This study makes use of one hundred pieces of data. According to the findings, most micro, small, and medium-sized enterprises (MSMEs) are confused about the meaning of accounting and its documentation. MSMEs are still reluctant to keep records because they still think that accounting is not important and is just a waste of time. The obstacles for MSME actors in implementing SAK EMKM are low understanding, awareness and also lack of socialization in the field of accounting.